Dual‐band frequency‐reconfigurable MIMO PIFA for LTE applications in mobile hand‐held devices. Issue 5 (17th February 2020) - Shruthi, G.; Yogesh Kumar, Choukiker
Abstract : In this study, dual‐port dual‐frequency tuneable MIMO planar inverted‐F antenna (PIFA) is presented for mobile hand‐held device applications. The proposed MIMO antenna consists of two symmetrical PIFAs with the centre‐to‐centre distance of 43.0 mm (0.1906 λ 0 ). The dual‐band tunability is achieved by changing the capacitance ( V 1 and V 2 ) of 4.15 pF (0 V)–0.72 pF (15 V). The impedance bandwidth of − 6 dB is realised from 0.8 to 0.98 GHz for the lower band and 1.65 to 2.2 GHz for the higher band. The proposed antenna provides the independent frequency tunability without disturbing the frequency bands. It shows the good isolation for both the tuneable bands > 20 dB without using any coupling element between the antenna structure. It has a peak realised gain of 3.44 dBi, good efficiency of > 75 % and envelope correlation coefficient of 0.007. In addition, the proposed PIFA performance is analysed with total active reflection coefficient, channel capacity, diversity gain, multiplexing efficiency, mean effective gain and specific absorption ratio for the tuneable range of frequencies. The good agreement is obtained between simulation and experimental performances to validate the antenna parameters.